Increasing environmentally friendly behavior in SMP N 13 Surakarta students through sociodrama and creative work - Maulydia Dwi Astuti; Emamiridya Erine Yupi; Tri Pujiati Sholikhah; Sri Lestari (Universitas Muhammadiyah Magelang, 2024)
Community service aims to enhance and instill students' awareness of the importance of environmental-friendly behavior through training and creative works at SMP Negeri 13 Surakarta. Sixteen students participated in this activity. The method employed in this community service is fostering environmental care attitudes through sociodrama and creative works. Before and after the training, students were given questionnaires to express their attitudes towards environmental-friendly behavior. The results of the activity show a t-test value with a significance level (2-tailed) of 0.01, indicating a difference in environmental care attitudes before and after the training. This means that sociodrama and creative works training can enhance the environmental-friendly behavior of SMPN 13 Surakarta students. The change in students' behavior persists even after the training, as evidenced by the repeated use of items such as water bottles or food containers for school meals.